Analisis Dampak Implementasi Integrasi Antarmoda Terhadap Loyalitas Pengguna Jasa Transportasi Dengan Mediasi Kepuasan Penumpang: Studi Kasus Pt. Mrt Jakarta Stasiun Asean Dan Integrasi Antarmoda CSW - Azra, Ichlasul Amal Nur; Fadhil, Dimas Nu’man; Marpaung, Edward (Jurnal Sistem Transportasi & Logistik, 2023)
This study aims to analyze the impact of the implementation of Intermodal Integration on Passenger Satisfaction and its Influence on the Loyalty of Transportation Service Users based on the perceptions of MRT Jakarta Asean Station users. The results of this study indicate that in structure 1 it shows that the Implementation of Intermodal Integration has a simultaneous 40.3% impact on Passenger Satisfaction while partially the effect is 63.5%. In structure 2 the impact of Intermodal Integration and Passenger Satisfaction on Service User Loyalty is 33.9% simultaneously while partially the impact of Intermodal Integration on Service User Loyalty is 41.2% and the impact of Passenger Satisfaction on Service User Loyalty is only 22.6%. All influences are stated to be significant but the effect of Passenger Satisfaction on Service User Loyalty is not significant because the sig count is > 0.05. The indirect impact that occurs between Intermodal Integration on Service User Loyalty through Passenger Satisfaction is stated to have an impact/influence because t count 2.058 > t table 1.984. This means that there is an indirect impact from implementing CSW intermodal integration on the loyalty of users of transportation services, especially for MRT Jakarta passengers.